Quelle nouvelle histoire pour la recherche en communication ? Le cas de Walter Lippmann - Dominique Trudel (Communication)
Drawing from recent historical work on Walter Lippmann, this research brief discusses the epistemological and political issues related to the “new history” of communication research. Specifically, two new historical interpretations are challenged: first the framing of Lippmann as an heir of American pragmatism, and second an appraisal of Lippmann’s ideas as fundamentally democratic.